The internal armed conflict in Ecuador from the constitutional sphere - Párraga Macías, Vielka Marisol (2024)
On January 9, 2024 became a historic date for the Republic of Ecuador, when President Daniel Noboa recognized worldwide that the country faces an internal armed conflict. The declaration of a state of emergency not only alarmed the local population, but also served as a call for international help, revealing the severity of the internal war with criminal organizations that had subjugated Ecuadorian society. Although previous governments also declared states of emergency, they failed to stop the crime wave, making it necessary to implement a military emergency regime. The objective of the research was to analyze the declaration of internal armed conflict in Ecuador from a constitutional perspective, determining its scope and legal effects. A qualitative approach was applied that through documentary techniques allowed the analysis of information. The research had an interpretive design based on bibliography and documents. The result is that the declaration of internal armed conflict falls within what is defined by International Humanitarian Law as such, so that the intervention of military forces is essential to combat organized crime.